Hubungan Faktor Risiko Tuberkulosis Terhadap Kadar Vitamin D Serum Pada Penderita Tuberkulosis di RSUP Haji Adam Malik Medan Dan Puskesmas Kota Medan Tahun 2019 - Fadlan Hafizh Harahap (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
Background: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis which attacks various organs. Tuberculosis has risk factors for age, sex, nutritional status, HIV infection, history of diabetes, corticosteroid use, and history of primary TB. Prolonged tuberculosis causes a decrease in vitamin D levels in blood serum.Objective: This study aims to look at the association of risk factors to serum vitamin D levels in TB sufferersMethod: Research conducted is analytic with cross-sectional design. The sample of the study were 30 patients with TB in Haji Adam Malik General Hospital, Teladan and Amplas primary health center Medan who had met the inclusion and exclusion criteria. Results: Pearson correlation test showed there was an inverse correlation between BMI and vitamin D levels (p = 0.007; r = -0.482) and there was no significant relationship between age and vitamin D levels. Fisher exact test found no association between vitamin D levels on corticosteroid use (p = 1,000), history of diabetes (p = 0.469), HIV coinfection, and primary TB (p = 1,000). Conclusion: In conclusion, there is an inverse correlation between the BMI value and vitamin D levels. No association was found between vitamin D levels and age, corticosteroid use, and history of diabetes.